Effect of tool geometry on friction stir spot welding of polypropylene sheets - M. K. Bilici (eXPRESS Polymer Letters)
The effects of tool geometry and properties on friction stir spot welding properties of polypropylene sheets were studied. Four different tool pin geometries, with varying pin angles, pin lengths, shoulder diameters and shoulder angles were used for friction stir spot welding. All the welding operations were done at the room temperature. Lap-shear tensile tests were carried out to find the weld static strength. Weld cross section appearance observations were also done. From the experiments the effect of tool geometry on friction stir spot weld formation and weld strength were determined. The optimum tool geometry for 4 mm thick polypropylene sheets were determined. The tapered cylindrical pin gave the biggest and the straight cylindrical pin gave the lowest lap-shear fracture load.